The functional morphology of the kidney of the Cape fur seal, Arctocephalus pusillus (Schreber) - Bester, Marthan N.(Marthan Nieuwoudt) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1974.